Protein kinase activity associated with the purified rat hepatic glucocorticoid receptor. - Miller-Diener, A (1985)
The Mr 94,000 steroid binding component of rat hepatic glucocorticoid receptor purified 5000-fold under-goes calcium-stimulated phosphorylation in vitro by [gamma-32P]ATP. Exogenous histones can be phosphorylated by this preparation without calcium. Calmodulin did not stimulate phosphorylation of the glucocorticoid receptor beyond that obtained with calcium alone. Although the specific calmodulin inhibitor calmidazolium had no effect, trifluoperazine and chlorpromazine, nonspecific calmodulin inhibitors, abolished the calcium-dependent phosphorylation of receptor. EGTA blocks the effect of calcium; magnesium cannot substitute for calcium. Cyclic nucleotides (cAMP or cGMP) do not stimulate phosphorylation of the receptor in the absence of calcium. Phosphorylation of the glucocorticoid receptor is steroid dependent. Triamcinolone acetonide elicited activation and phosphorylation of receptor in the presence of calcium, whereas the antagonists progesterone, cortexolone, and beta-lapachone did not. Sodium molybdate, which blocks the thermal activation step, inhibits phosphorylation of the receptor. The activated form of the glucocorticoid receptor is required for phosphorylation to occur. The ATP analogues 8-azido-ATP or fluorosulfonylbenzoyl adenosine, inhibit phosphorylation of the Mr 94,000 component, implying the presence of an ATP binding site inherent to the receptor.